ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS PESERTA DIDIK DALAM DISCOVERY LINK MAP - Setiasari, Atmi; Marsitin, Retno; Fayeldi, Trija (Pi: Mathematics Education Journal, 2021)
The ability of students to express many ideas when solving mathematical problems is called mathematical creative thinking. The level of creative thinking ability is a criterion for understanding and analyzing the creativity of students. The purpose of this study is to classify students' creative thinking skills with a discovery link map model. This study uses a qualitative approach, with a descriptive-qualitative research type. The research subjects consisted of 19 students of class VIIA SMP PGRI 6 Malang, then 6 students were taken to be analyzed, because there were similarities in answers at each level. Accumulated scores were obtained from tests, interviews, and documentation. Test the correctness of the data obtained from the method triangulation technique. Values are analyzed through data reduction steps, data presentation and drawing conclusions. The results of the study included, in the fluency aspect, students were classified as quite creative with a percentage of 63.15%, in the flexibility aspect, students belonged to the creative criteria with a percentage of 73.68%, and in the aspect of authenticity, students belonged to the criteria. not creative with a percentage of 0%. The conclusion based on the results of the study showed that students' mathematical creative thinking abilities in the fluency aspect were classified as quite creative criteria. The flexibility aspect is classified as a creative criterion. The aspect of authenticity is classified as uncreative criteria.